In-depth study of the behaviour of the Rogowski coil for fast current pulses. (30th June 2022) - Nassisi, V.
Graphical abstract: Highlight: The article analyses the behaviour of a linear Rogowski coil applied to a flat transmission line for to study of electromagnetic stresses in biological samples. To develop the theory, I use the Laplace Transform. The device will be useful when the 5G communication mode generates new electromagnetic radiation. Abstract: New developments on Rogowski coil are presented due to the evolution of temporal shortening of the current pulses. Recently, to study biophysical stresses by electromagnetic pulses flat transmission lines are used. As a result, linear Rogowski coils for electrical current diagnostics have also been developed and applied. An electrostatic shield with a slim slit is used to protect the Rogowski coil. The presence of the slit is necessary to lead the input current around the coil. The response of the Rogowski coil on high frequency signals is influenced, not only by all inductances, the capacitance, the number of turns of the coil, the load resistance, but also by the small size of the slim slit operated on the metal shield. The new theory is able to justify the response of the device due to sub-ns pulses, 100 p s, on slit width. By the theory, the attenuation factor is dependent on the slit size. This behaviour was experimentally verified obtaining a value ranging from 15.6 A / V to 24.7 A / V . The longest measurable pulse was approximately 250 n s . The device is very interesting owing to the radiation of the 5G communication mode.